A Pragmatic Analysis of Speech Acts in Reagan’s First Inaugural Speech - Muhsen, Ra’aed Ibraheem; Smeer, Imad Hayef (Al-Adab Journal, 2022)
This paper is primarily concerned with analysing speech acts as a sequence manifested in Reagan’s First Inaugural Speech. It aims to analyse the whole five forms of speech acts pragmatically in identified political speech, as described by Searle, 1969 (assertive, directive, commissive, expressive and declarative). To this end, a mixed method research is used. Qualitative part is used to describe and analyse types of speech acts in the selected data using a proposed model of two theories. It merges the theory of speech acts of Searle (1969) and Ferrara's theory of speech acts within sequences (1980). The quantitative part analyses the frequencies and percentages of speech acts types. The findings indicated that the assertive speech act is most frequently used by president Reagan. Thus, the findings of the present study would help researchers who are concerned with the study of language particularly people engaged within specialization of pragmatics. In addition, the study might be a useful for EFL / ESL learners since it attempts to discover speech acts' types and subtypes.